ReDrawing of Narrative Boundaries: An Introduction - Frederick Luis Aldama (Studies in 20th & 21st Century Literature, 2017)
ReDrawing of Narrative Boundaries: An Introduction provides an overview of the comics studies field as it relates to discussions and debates regarding its relationship to the study of literature and the arts. It provides a snapshot of today's comics studies field, including how the scholarly essays collected for this special issue, “A Planetary Republic of Comic Book Letters: Drawing Expansive Narrative Boundaries," work to deepen and widen our understanding of comics, and comics from all over the planet. Individually and collectively they eschew the lean toward the fill-in-the-blank (lit, film, etc.) comparisons, and instead excavate and theorize comics on their own terms.
Keywords: comics studies; global comics; cultural studies